Optimization of process conditions of lipase production from coconut dregs by solid-state fermentation - Vasudevan,Nittiyah (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Lipases comprise a group of hydrolytic enzymes which catalyze the hydrolysis and synthesis of triacylglycerides in the oil water interface. Screening of microorganism for extracellular lipase production from coconut dregs was conducted by using Aspergillus niger and Rhizopus oligosporus. The result shows that Rhizopus oligosporus able to produce higher lipase, 0.1527 U/mL compared to Aspergillus niger and thus it was chosen for further analysis. Process conditions such as pH, temperature and moisture content which influence the growth and production of lipase were studied. Central-Composite Design (CCD) of Response Surface approach was used to analyze the results and the optimum conditions for lipase production was determined. According to CCD, the optimum process conditions for Rhizopus oligosporus to produce lipase were as follow: 34.8 C, pH 5.24 and 62 % of moisture content. Validation process was carried out for 10 days under these conditions and it gives the maximum lipase activity at day 6 (0.2281 U/mL) . The standard error between optimization and validation was 2.23 %.